2019
DOI: 10.3389/fphar.2019.00958
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia bicolor (Euphorbiaceae) Latex Phytochemicals Induce Long-Lasting Non-Opioid Peripheral Analgesia in a Rat Model of Inflammatory Pain

Abstract: The negative side effects of opioid-based narcotics underscore the search for alternative non-opioid bioactive compounds that act on the peripheral nervous system to avoid central nervous system-mediated side effects. The transient receptor potential V1 ion channel (TRPV1) is a peripheral pain generator activated and sensitized by heat, capsaicin, and a variety of endogenous ligands. TRPV1 contributes to peripheral sensitization and hyperalgesia, in part, via triggering the release of proinflammatory peptides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 90 publications
2
5
0
Order By: Relevance
“…E . bicolor latex extract significantly reduced orofacial mechanical sensitivity in male rats ( F (1, 18) = 38.6; p ≤ 0.05) at 24 hours (Figure 2(a)) and in female rats ( F (1, 18) = 15.71; p ≤ 0.05) at 72 hours (Figure 2(b)) as compared to vehicle-treated rats and in accordance with our previous timeline of analgesia in hindpaw-inflamed rats [34]. In male rats, extract treatment significantly increased the withdrawal threshold from 0.6 g to 4.4 g, and in female rats, extract treatment significantly increased the withdrawal threshold from 0.74 g to 4.7 g. No significant differences were observed between the vehicle- and extract-treated groups at 1 and 6 hours in male and at 1, 6, and 24 hours in female rats ( p > 0.05).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…E . bicolor latex extract significantly reduced orofacial mechanical sensitivity in male rats ( F (1, 18) = 38.6; p ≤ 0.05) at 24 hours (Figure 2(a)) and in female rats ( F (1, 18) = 15.71; p ≤ 0.05) at 72 hours (Figure 2(b)) as compared to vehicle-treated rats and in accordance with our previous timeline of analgesia in hindpaw-inflamed rats [34]. In male rats, extract treatment significantly increased the withdrawal threshold from 0.6 g to 4.4 g, and in female rats, extract treatment significantly increased the withdrawal threshold from 0.74 g to 4.7 g. No significant differences were observed between the vehicle- and extract-treated groups at 1 and 6 hours in male and at 1, 6, and 24 hours in female rats ( p > 0.05).…”
Section: Resultssupporting
confidence: 90%
“…In the present study, E . bicolor latex extract significantly reduced orofacial mechanical sensitivity in both male and female rats at 24 hours and 72 hours, respectively, which correspond to the same onset time of analgesia observed in our previous studies on hindpaw-inflamed male and female rats [34]. In support, a recent systematic review reported that extracts from various plants are quite effective at alleviating orofacial pain in preclinical experimental models [59].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations